Implementasi Algoritma Yolo untuk Deteksi Tanaman Apotik Hidup - Peri Arta Wijaya, I Kadek; Astawa, I Gede Santi (Jurnal Nasional Teknologi Informasi dan Aplikasnya, 2025)
Living apothecary is a plant that is used to provide natural treatment or medicine. Therefore, to distinguish these plants, we carry out detection to distinguish live pharmaceutical plants. In this research we used (You Only Look Once) YOLOv8, Google Colab, Roboflow. Where we get the database from Google then we process the image using Roboflow then we create (You Only Look Once) YOLOv8, and we test it on Google Colab. The results of this research confirm that the YOLOv8 (You Only Look Once) algorithm in identifying and modeling 13 plant objects with a total of 1204 images obtained a precision percentage value of 59%, recall of 58%, and a MAP value of 60%, so the average value the accuracy is above 59%. In addition, it provides important contributions in the field of image recognition and visual data processing obtained through the application of the YOLOv8 algorithm to the problem of identifying objects in images.